2016
DOI: 10.1039/c5nr06602f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a 3D rGO–collagen hybrid scaffold for enhancement of the neural differentiation of mesenchymal stem cells

Abstract: The cell-material interface is one of the most important considerations in designing a high-performance tissue engineering scaffold because the surface of the scaffold can determine the fate of stem cells. A conductive surface is required for a scaffold to direct stem cells toward neural differentiation. However, most conductive polymers are toxic and not amenable to biological degradation, which restricts the design of neural tissue engineering scaffolds. In this study, we used a bioactive three-dimensional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 34 publications
2
103
0
Order By: Relevance
“…GO was prepared by the modified Hummers’ method as described in our previous work 3 , the GO nanosheets used for the preparation of the nanostructured rGO microfibers are approximately 1.5 nm thick and range from 1~4 μm in size (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO was prepared by the modified Hummers’ method as described in our previous work 3 , the GO nanosheets used for the preparation of the nanostructured rGO microfibers are approximately 1.5 nm thick and range from 1~4 μm in size (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the limited regenerative capabilities of the nervous system, stem-cell-based NTE has shown great potential for nerve regeneration by taking advantage of the self-renewal and differentiation capabilities of stem cells 2 , such as mesenchymal stem cells (MSCs) 3 and NSCs 4 . A microscale fiber-shaped structure, which can act as a physical graft for axon growth between the nerve sites, is one of the most typical biological components in nerve tissue 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Several promising results have also been reported when applying rGO in tissue engineering applications using electrical excitable cells. For neural tissue engineering applications, Guo et al reported that conductive rGO nanosheets on the surface of the porcine acellular dermal matrix could promote MSC differentiation into neuronal cells, under neural differentiation conditions, with higher protein and gene expression levels after 7 days . The potential of rGO for MI treatment has been investigated in many studies .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, scaffolds that support neural growth can be made of porous foams and membranes alone or loaded with a variety of GBNs and CNTs (Ramanathan et al, 2008; Chao et al, 2010; Alvarez et al, 2013; Li et al, 2013; Shah et al, 2014; Song et al, 2014; Weaver and Cui, 2015; Akhavan et al, 2016; Guo et al, 2016b,c). Moreover, there is evidence indicating that graphene and GBNs can serve as substrates for neural stem cells (NSC) differentiation, neuronal and oligodendrocyte growth, and the formation of neural circuits in cell culture ( in vitro) (Li et al, 2011, 2013; Park et al, 2011; Akhavan and Ghaderi, 2013a,b, 2014; Lorenzoni et al, 2013; Solanki et al, 2013; Tang et al, 2013; Akhavan et al, 2014, 2015; Shah et al, 2014).…”
Section: Introductionmentioning
confidence: 99%